B.4 Use of Health Care Resources by Pediatric Headache Patients: A population-based cohort study In the Province of Alberta. (November 2021) - Rajapakse, T; Bakal, J; Mailo, J; Nabipoor, M; Kassiri, J; Richer, L
Abstract : Background: Headache is a prevalent and disabling condition in children. It is a frequent cause of medication and health resource use in children. We examined the incidence and nature of health service use of the pediatric patient population in Alberta using provincial linked administrative databases. Methods: We used linked administrative data to identify patients under the age of 18 years from 2010-2017 and ICD-10 headache type at diagnosis and health service utilization including cost, medication use, outpatient/ED visits and hospitalizations. Patient geographic location was mapped. We explored health system use in the 3 years before and after diagnosis by identifying visits to community physicians, outpatient clinics emergency departments an inpatient admissions. Results: Over the 7 year study period 45, 454 patients were identified under 18 years, 60% of patients first diagnosed with migraine, 11.7% (5308) with tension headache and 28.2 (12, 833) with unspecified headache. Higher health system utilization seen immediately before and after headache diagnosis, returning to pre-diagnosis values within the 3 years following. Conclusions: This is the first population based reporting of pediatric headache prevalence and health resource utilization in Alberta. This contemporary prevalence and health resource data use should help inform future policy and headache care in the province of Alberta.